A study of risk factors for tuberculous meningitis among patients with tuberculosis in China: An analysis of data between 2012 and 2019 - Huang, Mailing; Ma, Yan; Ji, Xinyu; Jiang, Hui; Liu, Fangchao; Chu, Naihui; Li, Qi (Frontiers in Public Health, 2023)
Purpose The present study aimed to explore the risk factors for tuberculous meningitis (TBM) among patients with tuberculosis (TB). Methods This retrospective study was conducted on patients with TB who were hospitalized in Beijing Chest Hospital between January 2012 and December 2019. Demographic and clinical data of patients with TB were extracted from electronic medical records using a standardized data collection system. Logistic regression was used to analyze the risk factors associated with TBM. Results Of the total number of 22,988 cases enrolled, 3.1% were cases of TBM, which included 127 definite and 581 probable TBM, respectively. Multivariate analysis showed that definite TBM was significantly associated with patients aged < 30 years [adjusted odds ratio (aOR) = 3.015, 95% confidence interval (CI): (1.451–6.266)], who were farmers [aOR = 1.490, 95%CI: (1.020–2.177)], with miliary pulmonary TB [aOR = 105.842, 95%CI: (71.704–156.235)], and with malnutrition [aOR = 2.466, 95%CI: (1.110–5.479)]. Additionally, probable TBM was significantly associated with patients aged < 30 years [aOR = 2.174, 95% CI: (1.450–3.261)], aged 30–59 years [aOR = 1.670, 95% CI: (1.222–2.282)], who were farmers [aOR = 1.482, 95%CI: (1.203–1.825)], with miliary pulmonary TB [aOR = 108.696, 95%CI: (87.122–135.613)], and with a digestive system TB [aOR = 2.906, 95%CI: (1.762–4.793)]. Conclusion An age of < 30 years, being a farmer, and having miliary pulmonary TB were risk factors for TBM among patients with TB. Further screening of patients with TB with aforementioned characteristics could facilitate clinicians to identify patients with TBM at an early stage.